Rectal swab DNA collection protocol for PCR genotyping in rats - Audrey E Kaye; Jacob W Proctor-Bonbright; Jai Y Yu (BioTechniques)
DNA collection is essential for genotyping laboratory animals. Common collection methods require tissue amputation, causing discomfort and injury. Rectal swabbing has been proposed as an effective, minimally invasive alternative, but an evidence-backed protocol for the technique remains unavailable. This report evaluates the effects of collection parameters on the quality of PCR results and presents a protocol for genotyping a litter of rats within 3–5 h. Samples with 2–8 scrapes produced enough DNA to amplify targets up to ∼1800 bp long using PCR. Rectal swabbing produced PCR results with similar utility as ear clip samples, and results were unaffected by residual fecal matter or cell debris. The protocol enables fast, minimally invasive and repeatable genotyping using commercial PCR reagents.